2013
DOI: 10.1007/s00380-013-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cardiac magnetic resonance imaging versus baseline endomyocardial biopsy for the prediction of left ventricular reverse remodeling and prognosis in response to therapy in patients with idiopathic dilated cardiomyopathy

Abstract: Endomyocardial biopsy (EMB) and late gadolinium enhancement cardiovascular magnetic resonance (LGE-CMR) imaging performed at baseline are both used to evaluate the extent of myocardial fibrosis. However, no study has directly compared the effectiveness of these diagnostic tools in the prediction of left ventricular reverse remodeling (LVRR) and prognosis in response to therapy in patients with idiopathic dilated cardiomyopathy (IDCM). Seventy-five patients with newly diagnosed IDCM who were undergoing optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 37 publications
(42 reference statements)
0
10
1
1
Order By: Relevance
“…LGE-CMR imaging can detect the presence and extent of myocardial fibrosis possibly leading to SWMA. 13,14) However, our study did not show a significant difference in the LGE-CMR findings between the SWMA+ and SWMA-groups. To compare individually the region of SWMA by LVG and the LGEpositive area by CMR in this study, SWMA corresponded to LGE in some areas but not in other regions (data not shown).…”
Section: Discussioncontrasting
confidence: 76%
“…LGE-CMR imaging can detect the presence and extent of myocardial fibrosis possibly leading to SWMA. 13,14) However, our study did not show a significant difference in the LGE-CMR findings between the SWMA+ and SWMA-groups. To compare individually the region of SWMA by LVG and the LGEpositive area by CMR in this study, SWMA corresponded to LGE in some areas but not in other regions (data not shown).…”
Section: Discussioncontrasting
confidence: 76%
“…The majority of studies evaluated the presence or absence of LGE by visual analysis. 4,6,7,10,[13][14][15][16][17][18][19][20]22,[24][25][26][27][28][29]30,32 Duration of follow-up ranged from 1 year to 5.3 years; mean follow up was 3 years. The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The contrast-enhanced T1 mapping provides quantification of the degree of (146). Importantly, the extent of fibrosis, focal and/or diffuse, determines in part the likelihood of positive remodeling in response to treatment, suggesting that fibrosis might be used for risk stratification and decision making (147)(148)(149)(150)(151). Therefore, the extend and progression of cardiac fibrosis, as a consequence of myocardial infarction and/or chronic volume overload in patients with secondary MR, could be used as risk marker in this population: the benefit of intervention may be variable according to the presence and amount of fibrosis, as well as its progression over time.…”
Section: Comprehensive LV Evaluationmentioning
confidence: 99%